Factors affecting outdoor physical activity in extreme temperatures in a sub-tropical Chinese urban population: an exploratory telephone survey - Janice Y. Ho; Holly Y. C. Lam; Zhe Huang; Sida Liu; William B. Goggins; Phoenix K. H. Mo; Emily Y. Y. Chan (BMC, 2023)
Abstract Background Physical activity (PA) can be affected by extreme temperatures, however fewer studies have identified factors impacting this relationship. This study sought to identify factors associated with changes of outdoor PA during extreme cold/heat events in a sub-tropical Chinese urban population, including factors of sociodemographic, health conditions, temperature-related awareness and attitude, and protective behaviours. Methods Two telephone surveys were conducted a week after extreme cold/heat events in 2016 and 2017 among a cohort of Hong Kong residents over age 15. Data was collected on self-reported changes in outdoor PA level during the periods of extreme temperatures, health status, comorbidities, sociodemographic, and temperature-related awareness, and behavioural variables. We conducted multivariable logistic regression analyses to assess predictors of change in outdoor PA over the two extreme temperature events. Results and Conclusion: Among 435 participants (42.8% response rate), over a third of the participants reported decreased outdoor PA level in extreme temperature events, while 10% reported an increase in extreme heat. Self-reported cardiovascular diseases were associated with decreased PA level in extreme cold, while hypertension was associated with unchanged/increased PA level in extreme heat. These results suggest physical activity to be an important consideration in the understanding of climate change-and-health pathways and meriting further research.